Surface treatment method of copper foil, antioxidant copper foil and negative electrode of lithium battery

By surface treatment of the copper foil with antioxidant liquid composed of chromic acid compounds, aminotetrazole compounds and nitrogen-containing heterocyclic compounds, the antioxidant layer with chromium and nitrogen elements is formed, which solves the problem of oxidation of copper foil at high temperatures and improves its heat resistance, and is suitable for the negative electrode material of lithium batteries.

CN119710665APending Publication Date: 2025-03-28NANYA PLASTICS CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311360013.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-10-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing copper foil is prone to oxidation in high temperature environments, resulting in poor heat resistance, and its antioxidant layer contains nickel and zinc, which affects the performance and stability of lithium batteries.

Method used

The copper foil is surface treated with an antioxidant solution composed of chromic acid compounds, aminotetrazole compounds and nitrogen-containing heterocyclic compounds to form an antioxidant layer with chromium and nitrogen elements. The method includes immersing the copper foil substrate into the antioxidant liquid, forming an antioxidant layer, and ensuring the thickness and density of the antioxidant layer through specific electroplating conditions and processing time.

Benefits of technology

The color difference ΔE of the copper foil after baking at 250°C for 10 minutes is achieved, which significantly improves the heat resistance of the copper foil and avoids the negative impact of nickel and zinc on lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710665A_ABST
    Figure CN119710665A_ABST
Patent Text Reader

Abstract

The invention discloses a surface treatment method of a copper foil, an antioxidant copper foil and a negative electrode of a lithium battery. The anti-oxidation copper foil comprises a copper foil base material and an anti-oxidation layer formed on the copper foil base material. The anti-oxidation layer has a chromium element and is derived from a chromic acid compound, and the anti-oxidation layer has a nitrogen element which is at least partially derived from an aminotetrazole compound and a nitrogen-containing heterocyclic compound. The anti-oxidation copper foil has the following characteristics: (a) the chromium content of the anti-oxidation layer measured by XRF (X-Ray Fluorescence) is 5-35 [mu] g / m < 2 >; (b) the nitrogen content of the anti-oxidation layer measured by XPS is 0.1-10% by mass; (c) analyzing the antioxidant copper foil by headspace-MS (Mass Spectrometry) to determine a C-N signal; and (d) the color difference [Delta] E of the antioxidant copper foil baked at 250 DEG C for 10 minutes is not more than 8. Therefore, the antioxidant copper foil disclosed by the invention has more outstanding heat resistance, so that the antioxidant copper foil is more suitable for being used as a negative electrode material of a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper foil, and in particular to a surface treatment method of copper foil, an anti-oxidation copper foil, and a negative electrode of a lithium battery. Background Art

[0002] In the development of existing copper foil technology, the formation of an anti-oxidation layer on the surface of the copper foil is the key to protecting the copper foil from oxidation. If the anti-oxidation layer is not formed on the surface of the copper foil, the surface of the copper foil is easily oxidized at room temperature or high temperature atmosphere, so that the copper foil cannot be stored for a long time and is not suitable for operations that experience high temperatures (that is, the heat resistance of the copper foil is poor).

[0003] The conventional method of forming an anti-oxidation layer on the surface of copper foil is to form a nickel (Ni) electroplating layer, a zinc (Zn) electroplating layer, or a nickel-zinc (Ni-Zn) alloy electroplating layer by electroplating.

[0004] However, the copper foil with the anti-oxidation layer containing metal elements (such as nickel and zinc) is not suitable for lithium battery applications. If the copper foil is used in lithium batteries, the performance and stability of the lithium batteries may be reduced due to the metal elements such as nickel and zinc.

[0005] In order to apply copper foil to lithium batteries, the prior art has developed a copper foil with chromic acid and glucose as the components of the anti-oxidation layer, so that the copper foil is not easily oxidized at room temperature, and the color difference ΔE of the copper foil can be less than 8 after being heated at an operating temperature of 180°C for 10 minutes. In other words, the copper foil has a certain degree of heat resistance. However, the copper foil using chromic acid and glucose as the components of the anti-oxidation layer still has a color difference ΔE greater than 8 at a higher temperature (such as 250°C), which limits its application. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a surface treatment method of copper foil and an anti-oxidation copper foil to address the deficiencies of the prior art, which can have better heat resistance. For example, after the copper foil provided by the present invention is baked at an operating temperature of 250° C. for 10 minutes, the color difference ΔE of the copper foil can still be less than 8.

[0007] That is, compared with the copper foil in the prior art using chromic acid and glucose as components of the anti-oxidation layer, the copper foil of the present invention has a more outstanding heat resistance.

[0008] In order to solve the above technical problems, one of the technical solutions adopted by the present invention is to provide a surface treatment method for copper foil, including providing a copper foil substrate; immersing the copper foil substrate in an antioxidant solution containing a chromic acid compound, an aminotetrazole compound, and a nitrogen-containing heterocyclic compound; soaking or electroplating the copper foil substrate in the antioxidant solution for a predetermined time to form an antioxidant layer on at least one side of the copper foil substrate, thereby forming an antioxidant copper foil. The antioxidant copper foil satisfies the following characteristics: (a) the chromium content of the antioxidant layer measured by an X-ray fluorescence spectrometer (XRF) is between 5 μg / m 2 Up to 35 μg / m 2 ; wherein the chromium element in the antioxidant layer is derived from the chromic acid compound; (b) the nitrogen content of the antioxidant layer is between 0.1 mass % and 10 mass % as measured by X-ray photoelectron spectrometer (XPS); wherein the nitrogen element in the antioxidant layer is at least partially derived from the aminotetrazole compound and the nitrogen-containing heterocyclic compound; (c) the antioxidant copper foil can be analyzed by headspace-MS to determine the CN signal; and (d) the antioxidant copper foil is baked at 250°C for 10 minutes, and the color difference ΔE of the surface of the antioxidant layer before and after baking is not greater than 8.

[0009] Preferably, in the antioxidant solution, the concentration of the chromic acid compound is between 0.1 g / L and 5 g / L.

[0010] Preferably, the chromic acid compound is at least one selected from the group consisting of chromic acid, dichromic acid, and potassium dichromate.

[0011] Preferably, in the antioxidant liquid, the concentration of the aminotetrazolyl compound is between 0.1 g / L and 10 g / L, the concentration of the nitrogen-containing heterocyclic compound is between 0.1 g / L and 10 g / L, and the mass ratio between the aminotetrazolyl compound and the nitrogen-containing heterocyclic compound is between 1:5 and 5:1.

[0012] Preferably, the aminotetrazole compound is 5-aminotetrazole, and the nitrogen-containing heterocyclic compound is a bicyclic nitrogen-containing heterocyclic compound.

[0013] Preferably, the nitrogen-containing heterocyclic compound is benzotriazole.

[0014] Preferably, the antioxidant solution 2 further comprises at least two of 1,5-diaminotetrazole, 2-amino-1,3,4-thiadiazole, and 3,5-diamino-1,2,4-triazole.

[0015] Preferably, the predetermined time for the copper foil substrate to be immersed in the antioxidant solution or electroplated is between 0.1 seconds and 10 seconds, and the electroplating condition is a current density between 0.1 and 5 ASD (A / dm 2 ).

[0016] In order to solve the above technical problems, another technical solution adopted by the present invention is to provide an anti-oxidation copper foil, comprising: a copper foil substrate; and an anti-oxidation layer formed on one side surface of the copper foil substrate; wherein the anti-oxidation layer has a chromium element and is derived from a chromic acid compound, and the anti-oxidation layer has a nitrogen element, which is at least partially derived from an aminotetrazolyl compound and a nitrogen-containing heterocyclic compound; wherein the anti-oxidation copper foil satisfies the following characteristics: (a) the chromium content of the anti-oxidation layer measured by an X-ray fluorescence spectrometer (XRF) is between 5 μg / m 2 Up to 35 μg / m 2 ; (b) the nitrogen content of the antioxidant layer measured by X-ray photoelectron spectrometer (XPS) is between 0.1 mass % and 10 mass %; (c) the antioxidant copper foil is analyzed by headspace-MS, and a CN signal can be determined; and (d) the antioxidant copper foil is baked at 250°C for 10 minutes, and the color difference ΔE of the surface of the antioxidant layer before and after baking is not greater than 8.

[0017] Preferably, the thickness of the copper foil substrate is between 1 micrometer and 10 micrometers, and the thickness of the anti-oxidation layer is between 1 nanometer and 100 nanometers.

[0018] In order to solve the above technical problem, another technical solution adopted by the present invention is to provide a negative electrode of a lithium battery, which comprises the above-mentioned anti-oxidation copper foil.

[0019] One of the beneficial effects of the present invention is that the surface treatment method of copper foil, the anti-oxidation copper foil, and the negative electrode of lithium battery provided by the present invention can be achieved through "the anti-oxidation copper foil comprises a copper foil substrate and an anti-oxidation layer formed on the copper foil substrate. The anti-oxidation layer has a chromium element and is derived from a chromic acid compound, and the anti-oxidation layer has a nitrogen element, which is at least partially derived from an aminotetrazole compound and a nitrogen-containing heterocyclic compound" and "the anti-oxidation copper foil satisfies the following characteristics: (a) the chromium content of the anti-oxidation layer measured by XRF is between 5 and 35 μg / m 2; (b) the nitrogen content of the antioxidant layer determined by XPS is between 0.1 and 10 mass %; (c) the antioxidant copper foil can determine the CN signal through headspace-MS analysis; and (d) the color difference ΔE of the antioxidant copper foil baked at 250°C for 10 minutes is not greater than 8". The copper foil of the present invention has more outstanding heat resistance than the copper foil in the prior art using chromic acid and glucose as the antioxidant layer components, so that it is more suitable for use as a negative electrode material for lithium batteries, and the product can have a wider range of applications.

[0020] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the drawings provided are only for reference and description and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of a copper foil surface treatment method according to an embodiment of the present invention.

[0022] Figure 2 for Figure 1 Schematic diagram of an anti-oxidation layer formed on the surface of a copper foil.

[0023] Figure 3 It is a schematic diagram showing that an anti-oxidation layer is formed on one surface of the copper foil according to an embodiment of the present invention.

[0024] Figure 4 It is a schematic diagram of an embodiment of the present invention in which both sides of the copper foil have an anti-oxidation layer.

[0025] Figure 5 A schematic diagram of a variation of the copper foil surface treatment method according to an embodiment of the present invention.

[0026] Figure 6 Schematic diagram of another variation of the copper foil surface treatment method according to an embodiment of the present invention. DETAILED DESCRIPTION

[0027] The following is an explanation of the disclosed embodiments of the present invention through specific embodiments. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present invention. In addition, the drawings of the present invention are only simple schematic illustrations and are not depicted according to actual dimensions. It is stated in advance. The following embodiments will further explain the relevant technical contents of the present invention in detail, but the disclosed contents are not intended to limit the scope of protection of the present invention.

[0028] It should be understood that although the terms "first", "second", "third" and the like may be used herein to describe various materials or parameters, these materials or parameters should not be limited by these terms. These terms are mainly used to distinguish one material from another material, or one parameter from another parameter. In addition, the term "or" used herein may include any one or more combinations of the associated listed items depending on the actual situation.

[0029] [Surface treatment method of copper foil]

[0030] See also Figures 1 to 6 As shown, the embodiment of the present invention provides a surface treatment method for copper foil, which includes step S110, step S120, step S130, step S140, and step S150. It must be noted that the order of each step and the actual operation method recorded in this embodiment can be adjusted according to needs and are not limited to the description of this embodiment.

[0031] The step S110 includes: providing a copper foil substrate 1 (copper foil).

[0032] The copper foil substrate 1 may be, for example, an electrolytic copper foil or a rolled copper foil. In one embodiment, the copper foil substrate 1 is an electrolytic copper foil, and the copper foil substrate 1 is suitable for making a negative electrode of a lithium battery, but the present invention is not limited thereto.

[0033] The thickness of the copper foil substrate 1 may be, for example, between 1 and 10 micrometers, and preferably between 3 and 8 micrometers.

[0034] In some embodiments of the present invention, the step S110 further comprises: washing the copper foil substrate 1 with water to remove impurities or chemical residues on the surface of the copper foil substrate 1 .

[0035] The step S120 includes: disposing an antioxidant liquid 2 in the liquid storage tank T, and immersing the copper foil substrate 1 in the antioxidant liquid 2 (see Figure 1 shown).

[0036] The antioxidant solution 2 contains at least the following compounds (1) to (3):

[0037] (1) Chromic acid compounds;

[0038] (2) aminotetrazolyl compounds;

[0039] (3) Nitrogen-containing heterocyclic compounds.

[0040] Wherein, (1) the concentration of the chromic acid compound in the antioxidant solution is preferably between 0.1 g / L and 5 g / L, and particularly preferably between 0.1 g / L and 2 g / L.

[0041] In some embodiments of the present invention, the chromic acid compound is at least one selected from the group consisting of chromic acid, dichromic acid, and potassium dichromate.

[0042] Wherein, the chromic acid compound is preferably chromic acid.

[0043] The chemical formula of chromic acid is H2CrO4, and the chemical structure is as follows.

[0044]

[0045] The chemical formula of dichromic acid is H2Cr2O7, and the chemical structure is as follows.

[0046]

[0047] The chemical formula of potassium dichromate is K2Cr2O7, and the chemical structure is as follows.

[0048]

[0049] Specifically, the aminotetrazole compound (2) is 5-aminotetrazole, whose chemical formula is HN4CNH2 and whose chemical structure is as follows.

[0050]

[0051] The concentration of the aminotetrazole compound in the antioxidant solution is preferably between 0.1 g / L and 10 g / L, and particularly preferably between 2 g / L and 8 g / L.

[0052] Furthermore, (3) the nitrogen-containing heterocyclic compound is a bicyclic nitrogen-containing heterocyclic compound, and is preferably benzotriazole. The bicyclic nitrogen-containing heterocyclic compound may also be, for example, indoline or 1,4-diazabicycle, but the present invention is not limited thereto.

[0053] Among them, the chemical formula of benzotriazole is C6H5N3, and the chemical structure is as follows.

[0054]

[0055] The concentration of the nitrogen-containing heterocyclic compound in the antioxidant solution is preferably between 0.1 g / L and 10 g / L, and particularly preferably between 2 g / L and 8 g / L.

[0056] The mass ratio of the aminotetrazolyl compound to the nitrogen-containing heterocyclic compound is preferably between 1:5 and 5:1, and particularly preferably between 1:2 and 2:1. However, the present invention is not limited thereto.

[0057] The antioxidant solution 2 may further contain at least one of the following (4) to (6) amino-containing azole compounds:

[0058] (4) 1,5-diaminotetrazole;

[0059] (5) 2-amino-1,3,4-thiadiazole;

[0060] (6) 3,5-Diamino-1,2,4-triazole (1H-1,2,4-Triazole-3,5-diamine).

[0061] Among them, the chemical formula of 1,5-diaminotetrazole is CH4N6, and the chemical structure is as follows.

[0062]

[0063] The chemical formula of 2-amino-1,3,4-thiadiazole is C2H3N3S, and the chemical structure is as follows.

[0064]

[0065] The chemical formula of 3,5-diamino-1,2,4-triazole is C2H5N5, and the chemical structure is as follows.

[0066]

[0067] In some embodiments of the present invention, the antioxidant solution 2 comprises at least two of the following compounds: 1,5-diaminotetrazole, 2-amino-1,3,4-thiadiazole, and 3,5-diamino-1,2,4-triazole.

[0068] Furthermore, the total concentration of the amino-containing azole compounds (4) to (6) in the antioxidant solution is between 0.1 g / L and 100 g / L, and preferably between 1 g / L and 20 g / L.

[0069] The concentration of 1,5-diaminotetrazole is between 1 and 100 g / L, preferably between 1 and 10 g / L.

[0070] The concentration of 2-amino-1,3,4-thiadiazole is between 0.1 and 10 g / L.

[0071] The concentration of 3,5-diamino-1,2,4-triazole is between 0.1 and 10 g / L.

[0072] However, the present invention is not limited to the concentration ranges listed in the above examples.

[0073] In this embodiment, the liquid component of the antioxidant liquid 2 is water, such as deionized water (DI), reverse osmosis water (RO), or ultrapure water (MQ), but the present invention is not limited thereto.

[0074] The step S130 comprises: soaking or electroplating the copper foil substrate 1 in an antioxidant solution 2, so that an antioxidant layer 1a (such as Figure 2 and Figure 3 The thickness of the anti-oxidation layer 1a is between 1 and 100 nanometers, and preferably between 1 and 30 nanometers.

[0075] In another embodiment of the present invention, both sides of the copper foil substrate 1 are formed with an anti-oxidation layer 1a (such as Figure 4 ).

[0076] Specifically, the copper foil substrate 1 is immersed or electroplated in the anti-oxidation solution 2 for a predetermined time to form the anti-oxidation layer 1 a.

[0077] In some embodiments of the present invention, the predetermined time is between 0.1 seconds and 10 seconds, and preferably between 0.5 seconds and 5 seconds. For example, the predetermined time may be 0.3 seconds, 0.5 seconds, 1 second, 3 seconds, or 5 seconds. Furthermore, the electroplating condition of the copper foil substrate 1 in the antioxidant solution 2 is a current density between 0.1 and 5 ASD (i.e., A / dm 2 For example, the current density may be 0.5 ASD, 0.8 ASD, or 1 ASD.

[0078] It is worth mentioning that in this embodiment, the copper foil substrate 1 is described by taking a single copper foil immersed in the antioxidant solution 2 as an example, but the present invention is not limited thereto.

[0079] See also Figure 5 As shown, in one embodiment of the present invention, the copper foil substrate 1 is a continuous and rollable sheet. The copper foil substrate 1 can be guided into the antioxidant liquid 2 by a plurality of guide rollers R disposed in and around the liquid storage tank T.

[0080] Furthermore, the copper foil substrate 1 can be configured by adjusting the rolling speed of a plurality of guide rollers R so that the copper foil substrate 1 can stay in the antioxidant liquid 2 and be immersed in the predetermined time.

[0081] See also Figure 6 As shown, in another embodiment of the present invention, at least one pair of electrodes E is further disposed in the liquid storage tank T, so that the copper foil substrate 1 immersed in the antioxidant solution 2 can be electroplated by energizing the electrodes E. However, the present invention is not limited to the above manner.

[0082] The step S140 includes: taking out the copper foil substrate 1 with the anti-oxidation layer 1 a, and performing air blowing and drying to remove excess liquid components (such as water) in the anti-oxidation layer 1 a.

[0083] The step S150 includes: rolling up the copper foil substrate 1 having the anti-oxidation layer 1 a to complete the preparation of the anti-oxidation copper foil CF, but the present invention is not limited thereto.

[0084] [Anti-oxidation copper foil]

[0085] Please continue reading Figure 3 and Figure 4 As shown, the anti-oxidation copper foil CF or CF' provided in the embodiment of the present invention comprises: a copper foil substrate 1 and an anti-oxidation layer 1a (such as Figure 3 In another embodiment, both sides of the copper foil substrate 1 are formed with an anti-oxidation layer 1a (such as Figure 4 ).

[0086] The thickness of the copper foil substrate 1 may be, for example, between 1 and 10 micrometers, and preferably between 5 and 8 micrometers. The thickness of the anti-oxidation layer 1a may be between 1 and 100 nanometers, and preferably between 1 and 30 nanometers.

[0087] The anti-oxidation copper foil CF is suitable for the production of a lithium battery cathode, and the anti-oxidation copper foil CF has the following characteristics (a) to (d).

[0088] (a) The chromium content of the anti-oxidation layer 1a of the anti-oxidation copper foil CF measured by X-ray fluorescence spectrometer (XRF) is between 5 μg / m 2 (micrograms / square meter) to 35μg / m 2 , and preferably between 10 μg / m 2 Up to 30 μg / m 2The chromium element in the anti-oxidation layer 1a is derived from chromic acid compounds (ie, chromic acid compounds in the above-mentioned anti-oxidation solution, such as chromic acid, dichromic acid, and / or potassium dichromate).

[0089] It is worth mentioning that X-ray fluorescence spectrometer uses secondary X-rays excited by high-energy X-rays or gamma rays hitting materials for elemental analysis and chemical analysis, and can be used to quantify the chromium content in materials.

[0090] (b) The nitrogen content of the anti-oxidation layer 1a of the anti-oxidation copper foil CF measured by X-ray photoelectron spectroscopy (XPS) is between 0.1% and 10% by mass, preferably between 0.1% and 5% by mass, and more preferably between 0.1% and 2% by mass. The nitrogen element in the anti-oxidation layer 1a is at least partially derived from the aminotetrazole compound and the nitrogen-containing heterocyclic compound in the above-mentioned antioxidant solution, and the other part is derived from at least one of 1,5-diaminotetrazole, 2-amino-1,3,4-thiadiazole, and 3,5-diamino-1,2,4-triazole. It is worth mentioning that XPS is a quantitative energy spectrum technology for determining the elemental composition, empirical formula, and chemical state and electronic state of the elements contained therein in the material. This technology uses X-rays to irradiate the material to be analyzed, and simultaneously measures the kinetic energy and number of electrons escaping from the surface of the material within a range of 1nm to 10nm, thereby obtaining an X-ray photoelectron spectrum.

[0091] (c) The anti-oxidation copper foil CF can be analyzed by head space-MS / GC to determine the carbon nitrogen signal (CN signal). The determination method is, for example, to heat the anti-oxidation copper foil CF to 150°C to 250°C, and the gas generated by the sample enters the mass spectrometer for analysis to output the mass spectrum analysis results, and it can be evaluated whether the mass spectrum analysis results have a carbon nitrogen signal peak.

[0092] (d) The anti-oxidation copper foil CF is placed in an oven and baked at 250° C. for 10 minutes. A chromameter is used to observe whether the color difference ΔE of the surface of the anti-oxidation copper foil CF before and after baking is greater than 8.

[0093] According to the above configuration, the anti-oxidation copper foil CF is not easily oxidized at both room temperature and high temperature, and has better heat resistance than the copper foil in the prior art using chromic acid and glucose as anti-oxidation components.

[0094] It is worth mentioning that in the antioxidant solution 2 for forming the antioxidant layer 1a, the nitrogen-containing heterocyclic compound (such as benzotriazole) is the main component for forming the antioxidant layer 1a, which can provide the antioxidant layer 1a with basic antioxidant properties and heat resistance. The aminotetrazole compound (such as 5-aminotetrazole) is used to improve the density of the antioxidant layer 1a, thereby effectively assisting in improving the above antioxidant properties and heat resistance. The remaining amino-containing azole compounds in the antioxidant solution 2 can form a compound to strengthen the above antioxidant properties.

[0095] [Experimental data test]

[0096] Hereinafter, the content of the present invention will be described in detail with reference to Examples and Comparative Examples. However, the following Examples and Comparative Examples are only used to help understand the present invention, and the scope of the present invention is not limited to these examples.

[0097] Example 1: Prepare an antioxidant solution, which is an aqueous solution and contains: 0.6 g / L chromic acid, 5 g / L 5-aminotetrazole, 5 g / L benzotriazole, 2 g / L 1,5-diaminotetrazole, 5 g / L 2-amino-1,3,4-thiadiazole, and 2 g / L 3,5-diamino-1,2,4-triazole. Wash the copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) with water, and immerse the copper foil substrate in the above antioxidant solution. The copper foil substrate is immersed and electroplated for 0.5 seconds under the electroplating condition of a current density of 0.8 ASD, thereby forming an antioxidant layer on the surface of the copper foil substrate, and then obtaining an antioxidant copper foil. Then, the antioxidant copper foil is taken out from the antioxidant solution, air-dried, and rolled up to complete the preparation of the antioxidant copper foil.

[0098] In terms of test results, the chromium content of the anti-oxidation copper foil of Example 1 obtained by XRF analysis is 20 μg / m 2 The nitrogen content obtained by XPS analysis is 0.5 mass %, the CN signal can be obtained by headspace-MS analysis, and the color difference ΔE after baking at 250° C. for 10 minutes is not greater than 8. The anti-oxidation copper foil of Example 1 has better anti-oxidation properties and heat resistance.

[0099] Example 2: Prepare an antioxidant solution, which is an aqueous solution and contains: 0.6 g / L of chromic acid, 5 g / L of 5-aminotetrazole, 5 g / L of benzotriazole, 2 g / L of 2-amino-1,3,4-thiadiazole, and 5 g / L of 3,5-diamino-1,2,4-triazole. Wash the copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) with water, and immerse the copper foil substrate in the above antioxidant solution. The copper foil substrate is treated with an electroplating condition of a current density of 0.8 ASD for 0.5 seconds to form an antioxidant layer on the surface of the copper foil substrate, thereby obtaining an antioxidant copper foil. Then, the antioxidant copper foil is taken out of the antioxidant solution, air-dried, and rolled up to complete the preparation.

[0100] In terms of test results, the chromium content of the anti-oxidation copper foil of Example 2 obtained by XRF analysis is 20 μg / m 2 The nitrogen content obtained by XPS analysis is 0.5 mass %, the CN signal can be obtained by headspace-MS analysis, and the color difference ΔE after baking at 250° C. for 10 minutes is not greater than 8. The anti-oxidation copper foil of Example 2 has better anti-oxidation properties and heat resistance.

[0101] Example 3: Prepare an antioxidant solution, which is an aqueous solution and contains: 0.6 g / L of chromic acid, 5 g / L of 5-aminotetrazole, 5 g / L of 1,5-diaminotetrazole, 2 g / L of 2-amino-1,3,4-thiadiazole, and 2 g / L of 3,5-diamino-1,2,4-triazole, and the antioxidant solution does not contain benzotriazole. Wash the copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) with water, and immerse the copper foil substrate in the above antioxidant solution. Treat the copper foil substrate with an electroplating condition of a current density of 0.8 ASD for 0.5 seconds to form an antioxidant layer on the surface of the copper foil substrate, thereby obtaining an antioxidant copper foil. Then, take out the antioxidant copper foil from the antioxidant solution, air dry, and roll it up to complete the preparation of the antioxidant copper foil.

[0102] In terms of test results, the chromium content of the anti-oxidation copper foil of Example 3 obtained by XRF analysis is 20 μg / m 2 The nitrogen content obtained by XPS analysis is 0.5% by mass, and the CN signal can be obtained by headspace-MS analysis, and the color difference ΔE after baking at 250°C for 10 minutes is greater than 10. The antioxidant properties and heat resistance of the antioxidant copper foil of Example 3 are slightly worse than those of Examples 1 and 2. The reason may be that the density of the antioxidant layer is poor.

[0103] Example 4: Prepare an antioxidant solution, which is an aqueous solution and contains: 0.6 g / L of chromic acid, 5 g / L of benzotriazole, 2 g / L of 1,5-diaminotetrazole, 5 g / L of 2-amino-1,3,4-thiadiazole, and 2 g / L of 3,5-diamino-1,2,4-triazole, and the antioxidant solution does not contain 5-aminotetrazole. Wash the copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) with water, and immerse the copper foil substrate in the above antioxidant solution. Treat the copper foil substrate with an electroplating condition of a current density of 0.8 ASD for 0.5 seconds to form an antioxidant layer on the surface of the copper foil substrate, thereby obtaining an antioxidant copper foil. Then, take out the antioxidant copper foil from the antioxidant solution, air dry, and roll it up to complete the preparation of the antioxidant copper foil.

[0104] In terms of test results, the chromium content of the anti-oxidation copper foil of Example 4 obtained by XRF analysis is 20 μg / m 2The nitrogen content obtained by XPS analysis is 0.5% by mass, and the CN signal can be obtained by headspace-MS analysis, and the color difference ΔE after baking at 250°C for 10 minutes is greater than 10. The antioxidant properties and heat resistance of the antioxidant copper foil of Example 4 are slightly worse than those of Examples 1 and 2. The reason may be that the density of the antioxidant layer is poor.

[0105] Comparative Example 1: An antioxidant solution is prepared, which is an aqueous solution and contains: 0.6 g / L of chromic acid and 2 g / L of 3,5-diamino-1,2,4-triazole, and the antioxidant solution does not contain 5-aminotetrazole and benzotriazole. The copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) is washed with water, and the copper foil substrate is immersed in the above-mentioned antioxidant solution. The copper foil substrate is treated for 0.5 seconds under electroplating conditions of a current density of 0.8ASD to form an antioxidant layer on the surface of the copper foil substrate to obtain an antioxidant copper foil. Thereafter, the antioxidant copper foil is taken out of the antioxidant solution, air-dried, and rolled up to complete the preparation of the antioxidant copper foil. In terms of test results, the chromium content of the antioxidant copper foil of Comparative Example 1 obtained by XRF analysis is 20μg / m 2 The nitrogen content obtained by XPS analysis was 0 mass % (unable to be analyzed), no CN signal was obtained by headspace-MS analysis, and the color difference ΔE after baking at 250°C for 10 minutes was greater than 20. The antioxidant properties and heat resistance of the antioxidant copper foil of Comparative Example 1 are far inferior to those of Examples 1-2.

[0106] Comparative Example 2: An antioxidant solution is prepared, which is an aqueous solution and contains: 0.6 g / L of chromic acid and 2 g / L of 2-amino-1,3,4-thiadiazole, and the antioxidant solution does not contain 5-aminotetrazolyl and benzotriazole. The copper foil substrate (electrolytic copper foil, having a thickness of about 6 microns) is washed with water, and the copper foil substrate is immersed in the above antioxidant solution. The copper foil substrate is treated for 0.5 seconds under electroplating conditions of a current density of 0.8ASD to form an antioxidant layer on the surface of the copper foil substrate, thereby obtaining an antioxidant copper foil. Thereafter, the antioxidant copper foil is taken out of the antioxidant solution, air-dried, and rolled up to complete the preparation of the antioxidant copper foil. In terms of test results, the chromium content of the antioxidant copper foil of Comparative Example 2 obtained by XRF analysis is 20μg / m 2 The nitrogen content obtained by XPS analysis was 0 mass % (unable to be analyzed), no CN signal was obtained by headspace-MS analysis, and the color difference ΔE after baking at 250°C for 10 minutes was greater than 20. The antioxidant properties and heat resistance of the antioxidant copper foil of Comparative Example 2 are far inferior to those of Examples 1-2.

[0107] The above analysis methods for XRF analysis of chromium content, XPS analysis of nitrogen content, headspace-MS qualitative CN signal, and color difference ΔE have been explained above and will not be repeated here.

[0108] [Table 1]

[0109]

[0110]

[0111] From the above experimental results, it can be seen that the color difference ΔE of the antioxidant copper foil prepared in Examples 1 to 2 after baking at 250°C for 10 minutes is no more than 8, indicating that the antioxidant layer formed by the antioxidant solution containing both 5-aminotetrazole and benzotriazole (i.e., a bicyclic nitrogen-containing heterocyclic compound) can make the copper foil have better antioxidant and heat resistance.

[0112] [Beneficial Effects of Embodiments]

[0113] One of the beneficial effects of the present invention is that the surface treatment method of copper foil, the anti-oxidation copper foil, and the negative electrode of lithium battery provided by the present invention can be achieved through "the anti-oxidation copper foil comprises a copper foil substrate and an anti-oxidation layer formed on the copper foil substrate. The anti-oxidation layer has a chromium element and is derived from a chromic acid compound, and the anti-oxidation layer has a nitrogen element, which is at least partially derived from an aminotetrazole compound and a nitrogen-containing heterocyclic compound" and "the anti-oxidation copper foil satisfies the following characteristics: (a) the chromium content of the anti-oxidation layer measured by XRF is between 5 and 35 μg / m 2 ; (b) the nitrogen content of the antioxidant layer determined by XPS is between 0.1 and 10 mass %; (c) the antioxidant copper foil can determine the CN signal through headspace-MS analysis; and (d) the color difference ΔE of the antioxidant copper foil baked at 250°C for 10 minutes is not greater than 8". The copper foil of the present invention has a more outstanding heat resistance than the copper foil in the prior art using chromic acid and glucose as the antioxidant layer components, so that it is more suitable as the negative electrode material of lithium batteries and enables the product to have a wider range of applications.

[0114] The contents disclosed above are only preferred feasible embodiments of the present invention, and are not intended to limit the scope of the present invention. Therefore, all equivalent technical changes made using the contents of the present invention description and drawings are included in the scope of the present invention.

Claims

1. A surface treatment method for copper foil, characterized in that: The surface treatment method of the copper foil comprises: providing a copper foil substrate; Immersing the copper foil substrate in an antioxidant solution containing a chromic acid compound, an aminotetrazole compound, and a nitrogen-containing heterocyclic compound; Allowing the copper foil substrate to soak or electroplate in the anti-oxidation solution for a predetermined time to form an anti-oxidation layer on at least one side of the copper foil substrate, thereby forming an anti-oxidation copper foil; Wherein, the anti-oxidation copper foil meets the following characteristics: (a) The chromium content of the anti-oxidation layer measured by X-ray fluorescence spectrometer is between 5 μg / m 2 Up to 35 μg / m 2 ; wherein the chromium element in the anti-oxidation layer is derived from the chromic acid compound; (b) the nitrogen content of the antioxidant layer measured by an X-ray photoelectron spectrometer is between 0.1 mass % and 10 mass %; wherein the nitrogen element in the antioxidant layer is at least partially derived from the aminotetrazolyl compound and the nitrogen-containing heterocyclic compound; (c) the anti-oxidation copper foil can be analyzed by headspace-MS to determine the CN signal; and (d) The anti-oxidation copper foil is baked at 250° C. for 10 minutes, and the color difference ΔE of the surface of the anti-oxidation layer before and after baking is not greater than 8.

2. The surface treatment method of copper foil according to claim 1, characterized in that: In the antioxidant solution, the concentration of the chromic acid compound is between 0.1 g / L and 5 g / L, and the chromic acid compound is at least one selected from the group consisting of chromic acid, dichromic acid, and potassium dichromate.

3. The surface treatment method of copper foil according to claim 1, characterized in that: In the antioxidant liquid, the concentration of the aminotetrazolyl compound is between 0.1 g / L and 10 g / L, the concentration of the nitrogen-containing heterocyclic compound is between 0.1 g / L and 10 g / L, and the mass ratio between the aminotetrazolyl compound and the nitrogen-containing heterocyclic compound is between 1:5 and 5:

1.

4. The surface treatment method of copper foil according to claim 3, characterized in that: The aminotetrazole compound is 5-aminotetrazole, and the nitrogen-containing heterocyclic compound is a bicyclic nitrogen-containing heterocyclic compound.

5. The surface treatment method of copper foil according to claim 4, characterized in that: The nitrogen-containing heterocyclic compound is benzotriazole.

6. The surface treatment method of copper foil according to claim 1, characterized in that: The antioxidant solution further comprises at least two of 1,5-diaminotetrazole, 2-amino-1,3,4-thiadiazole, and 3,5-diamino-1,2,4-triazole.

7. The surface treatment method of copper foil according to claim 1, characterized in that: The predetermined time for the copper foil substrate to be immersed or electroplated in the antioxidant solution is between 0.1 seconds and 10 seconds, and the electroplating condition is a current density between 0.1 and 5 A / dm 2 .

8. An anti-oxidation copper foil, characterized in that: The anti-oxidation copper foil comprises: Copper foil substrate; and An anti-oxidation layer is formed on one side surface of the copper foil substrate; The anti-oxidation layer contains chromium and is derived from chromic acid compounds, and the anti-oxidation layer contains nitrogen, which is at least partially derived from aminotetrazolyl compounds and nitrogen-containing heterocyclic compounds; Wherein, the anti-oxidation copper foil meets the following characteristics: (a) The chromium content of the anti-oxidation layer measured by X-ray fluorescence spectrometer is between 5 μg / m 2 Up to 35 μg / m 2 ; (b) the nitrogen content of the anti-oxidation layer measured by X-ray photoelectron spectrometer is between 0.1 mass % and 10 mass %; (c) the anti-oxidation copper foil can be analyzed by headspace-MS to determine the CN signal; and (d) The anti-oxidation copper foil is baked at 250° C. for 10 minutes, and the color difference ΔE of the surface of the anti-oxidation layer before and after baking is not greater than 8.

9. The oxidation-resistant copper foil according to claim 8, characterized in that: The thickness of the copper foil substrate is between 1 micrometer and 10 micrometers, and the thickness of the anti-oxidation layer is between 1 nanometer and 100 nanometers.

10. A negative electrode of a lithium battery, characterized in that: The negative electrode of the lithium battery comprises the oxidation-resistant copper foil according to any one of claims 8 and 9.

Citation Information

Cited By

  • Femtosecond laser additive manufacturing method for lithium-loving microstructure on surface of copper foil current collector for metal lithium negative electrode

    CN121700376A